Pulse-based cropping systems for soil health restoration, resources conservation, and nutritional and environmental security in rainfed agroecosystems - Kumar, Sandeep; Gopinath, K. A.; Sheoran, Seema; Meena, Ram Swaroop; Srinivasarao, Ch.; Bedwal, Sandeep; Jangir, Chetan Kumar; Mrunalini, Kancheti; Jat, Ramdhan; Praharaj, C. S. (Frontiers in Microbiology, 2023)
Pulses are an important source of energy and protein, essential amino acids, dietary fibre, minerals, and vitamins and play a significant role in addressing global nutritional security. The global pulse area, production, and average productivity increased from 1961 to 2020 (60-yrs). Yet, the global food supplies through pulses are negligible and merely 1.0% of the total food supply and 1.2% of the vegan food system. In this situation, protein-rich food is still a question on the global level to make a malnutrition-free world. Pulses are a vital component of agricultural biological diversity, essential for tackling climate change and energy diets for vegetarians. Pulses can mitigate climate change by reducing the dependence on synthetic fertilizers that artificially introduce nitrogen (N) into the soil. The high demand and manufacturing of chemical fertilizers emit greenhouse gases, and their overuse can harm the environment. In addition, increased demand for vegetal protein under most global agroecosystems is under a stressed rainfed situation. The rainfed agroecosystem is a shelter for the poor people of a significant part of the globe, like Africa, South Asia, and Latin America. Nearly 83% (over 1260 million ha) of cultivated land is under rainfed agriculture, significantly contributing to global food security by supplying over 60% of the food. In rainfed areas, the limitation of natural resources with the shrinking land, continuous nutrient mining, soil fertility depletion, declining factor productivity, constantly falling water availability, decreasing soil carbon (C) stock, augmented weed menace, ecological instability, and reduced system productivity are creating the more challenging situation. Pulses, being the crops of marginal and semi-marginal soils of arid and semi-arid climates, require less input for cultivation, such as water, nutrients, tillage, labour, energy, etc. Furthermore, pulses cultivation accommodation reduces groundwater exploitation, C and N footprints, agrochemical application in the cropping systems, and ill effects of climate change due to their inherent capacity to withstand harsh soil, phytoremediation properties, and stand well under the stressed environmental condition. Therefore, the pulses availability can be improved through horizontal and vertical expansion. This article focuses on pulses' roleecological services, human, soil, environmental health, and economic security for advanced sustainability